Interaction of granaticin B with the transcription system of Bacillus subtilis - Weiser, J; Janda, I; Mikulík, K; Tax, J (Folia microbiologica, 1977)
The interaction of granaticin B, a quinone antibiotic produced by Streptomyces granaticolor, with some biologically important bivalent metal ions, DNA and ATP was demonstrated spectrophotometrically. The activity of isolated RNA polymerase was higher when the DNA of phage SP 50 served as template than with DNA isolated from Bacillus subtilis. Granaticin B inhibited in vitro RNA synthesis, similarly to certain other antibiotics (the inhibition was three times lower than that caused by actinomycin D or streptolydigin and slightly higher than that by epsilon-pyrromycinone). The inhibitory effect was higher when the Mg2+ concentration in the reaction mixture was decreased. The inhibition was then proportional to the concentration of the DNA template. DNA-dependent RNA synthesis is thus inhibited in vitro by granaticin B but this does not appear to be the only site of action of this antibiotic in vivo.
Keywords: Bacillus subtilis; bakteriální RNA; DNA-Directed RNA Polymerases; adenosintrifosfát; DNA řízené RNA-polymerasy; Terpenes; terpeny; bakteriofágy; Transcription, Genetic; hořčík; Magnesium; genetické matrice; genetická transkripce; DNA; Benzofurans; spektrofotometrie; Adenosine Triphosphate; Spectrophotometry; Templates, Genetic; RNA, Bacterial; Bacteriophages; benzofurany